RATIO DECIDENDI TERHADAP PERBUATAN MELAWAN HUKUM YANG DILAKUKAN TERGUGAT I DAN TERGUGAT II KEPADA PENGGUGAT ATAS TINDAKAN WANPRESTASI (Putusan Mahkamah Agung Nomor 1682K/PDT/2020) - Zamroh, Alifatul Renawati; Handayati, Nur; Subekti; Soekorini, Noenik; Astutik, Sri (Jurnal Hukum Ius Publicum, 2024)
This study analyzes the decision of the Supreme Court of the Republic of Indonesia in the civil case No. 1682 K/Pdt/2020 involving Muhammad Hikman Ballagi as the Applicant and PT. Astra Sedaya Finance as the Defendant. The case focused on a dispute surrounding vehicle financing that caused material and intangible losses to the plaintiff. The study uses a normative jurisprudence method with a case approach to investigate various court decisions, ranging from the Kendari State Court, the South Eastern Sulawesi High Court, to the Supreme Court. The results of the investigation show that the Supreme Court rejected the petition of the plaintiff's cassation and sentenced him to pay the costs of the case at all levels of the court. The study provides insight into the legal considerations used by the courts in settling the financing of vehicles and its impact on the parties to the dispute. The dispute relates to a financing agreement with a trust guarantee between the plaintiff and the defendant. The case involves a judge's consideration of acts of non-performance, the seizure of a car without a detailed basis, and the obligation to pay monthly contributions. The judge also considers the legal protection of the parties as well as the principle of justice in determining the decision.